Karte des Meerbusens St. Laurenz und der benachbarten Lænder zur allgemeinen Historie der Reisen - Bellin, Jacques Nicolas, 1703-1772 (1757)
Black and white. Prime meridian Paris. Decorative title cartouche. Bar scale in French common leagues.